2x+3(5x-13)=12

Simple and best practice solution for 2x+3(5x-13)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(5x-13)=12 equation:


Simplifying
2x + 3(5x + -13) = 12

Reorder the terms:
2x + 3(-13 + 5x) = 12
2x + (-13 * 3 + 5x * 3) = 12
2x + (-39 + 15x) = 12

Reorder the terms:
-39 + 2x + 15x = 12

Combine like terms: 2x + 15x = 17x
-39 + 17x = 12

Solving
-39 + 17x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + 17x = 12 + 39

Combine like terms: -39 + 39 = 0
0 + 17x = 12 + 39
17x = 12 + 39

Combine like terms: 12 + 39 = 51
17x = 51

Divide each side by '17'.
x = 3

Simplifying
x = 3

See similar equations:

| r-40=-30 | | 64x^2-49= | | 16x^2-5x+1=0 | | 2x-45=10 | | 4x^2+12x+2=0 | | (5x-1)(4-4x)= | | 8x^2-31x=4 | | (4)y-8-3y+12=0 | | 24y^2-16y= | | 11x^2-4x=0 | | 2d-(6)=5 | | 92x=96 | | 4x+4.72=3x | | 2d-(d)=5 | | 3x+5=-14 | | x^2+14x+74=0 | | 8x-7=-2 | | 5x+7=9-39 | | 3x+2y+5x=12 | | -8(m-2)=-4 | | -4x(-6x-3)=12 | | .1818-x=.1x | | 28x^3-7x=0 | | 8v^2-98=0 | | (4)y-2(4)-3y+12=0 | | -6y+6=-4(2y+2) | | 2(x+1)=x-18 | | 4r^2-196=0 | | -5b+7b=8b-6 | | 3x+4=6x+1 | | -18a^2+128=0 | | (20x+3)(15x+2)(5x+11)(10x-6)= |

Equations solver categories